Integration of wordwall in mathematics learning: An efforts to improve students mathematical communication - Hijrah Nasution; Izwita Dewi; Hamidah Nasution (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2026)
Mathematical communication ability is an essential competency in mathematics learning because it enables students to express mathematical ideas, use representations, and explain solution procedures systematically. However, many students still experience difficulties in communicating mathematical ideas due to teacher-centered learning and limited interactive activities. This study aimed to examine the effectiveness of Wordwall-integrated mathematics learning on students’ mathematical communication ability. This study employed a quantitative quasi-experimental method with a pretest-posttest control group design. The population consisted of seventh-grade students at Yasiriyah Private Junior High School Medan, with a sample of 50 students divided into an experimental class and a control class, each consisting of 25 students. The research instrument was an essay test based on indicators of mathematical communication ability. Data were analyzed using descriptive statistics, N-Gain analysis, normality and homogeneity tests, and an independent sample t-test. The results showed that the experimental class achieved a higher improvement than the control class, with a mean N-Gain score of 0.74 in the high category, while the control class obtained 0.39 in the moderate category. The independent sample t-test showed a significance value of 0.000 < 0.05, indicating a significant difference between the two classes. Improvements were found in all indicators, with the highest improvement in explaining solution procedures systematically. These findings indicate that Wordwall-integrated mathematics learning is effective in improving students’ mathematical communication ability and can support more interactive and student-centered learning.